BUILDING SUSTAINABLE FUTURES: PROFILING SDGS UNDERSTANDING AND ESD INTEGRATION CAPACITY AMONG PRE-SERVICE PRIMARY SCHOOL TEACHERS - Kartono Kartono; Ricka Tesi Muskania; Oktavila Nauli Sinurat; Agatha Christie; Meli Meli (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to (1) empirically measure the level of Indonesian pre-service primary school teachers’ knowledge of Sustainable Development Goals (SDGs), (2) analyze variations in knowledge levels based on demographic and academic characteristics, and (3) statistically examine the relationship between SDG knowledge levels and pre-service primary school teachers’ ability to integrate Education for Sustainable Development (ESD) into science learning.Methodology – This study employed a quantitative descriptive, cross-sectional design. Empirical data were collected through a survey of 190 pre-service primary school teachers from 21 universities across Indonesia, selected through purposive sampling based on their completion of science education coursework. The research instrument was a 30-item SDG knowledge questionnaire. Data analysis involved descriptive and inferential statistics, including subgroup comparisons and the Chi-Square test of independence.Findings – The empirical findings indicate that pre-service primary school teachers’ SDG knowledge levels were predominantly in the good-to-very-good category (M = 24.74 out of 30). Variations across demographic and academic subgroups were relatively limited, with higher knowledge levels observed among respondents with science (IPA) and primary education (PGSD) backgrounds. The Chi-Square test revealed a statistically significant relationship between SDG knowledge and the ability to integrate ESD into science learning (p < 0.05).Contribution – This study provides quantitative empirical evidence of Indonesian pre-service primary school teachers' readiness to implement sustainability-oriented science instruction. The findings underscore the importance of systematically integrating SDGs and ESD into teacher education curricula to strengthen future teachers’ roles as evidence-based agents of change in advancing sustainable primary science education.